What do tertiary level students in the U.S.A. and Northern Ireland (UK) worry about? An exploratory study. Issue 4 (4th July 2018) - Brzezinski, Sara; Millar, Rob; Tracey, Anne
ABSTRACT: The purpose of this study is to determine the personal and social worries of samples of tertiary-level students in the U.S.A. and Northern Ireland (UK) using the Things I Worry About Scale (TIWAS). An online questionnaire, which included the TIWAS, was completed by two samples (U.S.A. = 71 and Northern Ireland = 187). Results indicate that students, in both locations, report worrying frequently about a similar broad range of issues, particularly the challenges of academic study and achievement, financial matters and future career possibilities. The needs of individual students who express frequent worrying about experiences 'sometimes' worried about by the majority are noted. The overall findings support perceptions that a majority of students are rather anxious, are under considerable pressure and worry very frequently.